KONSEP DASAR EVALUASI DALAM PAI - Yulianis, Yulianis; Julhadi, Julhadi (Ensiklopedia of Journal, 2026)
Learning evaluation in Islamic Religious Education (PAI) is a crucial aspect to ensure the achievement of educational objectives, which are not only oriented towards the cognitive domain, but also the affective and psychomotor domains. However, practice in the field shows that many educators still equate tests, measurements, assessments, and evaluations, resulting in a less comprehensive assessment process and inability to fully reflect student development. This study employed a qualitative-descriptive method through a literature review of educational evaluation theory books and relevant national and international journals to deeply analyze the basic concepts of evaluation and their urgency in Islamic Religious Education (PAI) learning. The results show that tests only function as measuring tools; measurements provide quantitative values; assessments gather comprehensive information about the learning process and outcomes; while evaluation is a comprehensive assessment of learning effectiveness. The main findings emphasize that evaluation in PAI must be carried out authentically, continuously, and touch on three competency domains in order to encourage the formation of Islamic character, improve the quality of the learning process, and provide a basis for improving teaching strategies. This article provides a theoretical contribution by clarifying the conceptual distinctions between these terms and offers a more relevant evaluation framework for PAI educators. Keywords: learning evaluation, assessment, testing, measurement, Islamic Religious Education, authentic, Islamic character